Titaniferous magnetite and barite from the San Gregorio de Polanco dike swarm, Paraná Magmatic Province, Uruguay - Rossana Muzio; Fernando Scaglia; Henri Masquelin (Earth Sciences Research Journal)
The San Gregorio de Polanco Dike Swarm (Tacuarembó Department, Uruguay) is the southernmost set of dikes in the Paraná Magmatic Province of Uruguay. Five major dikes have been identified with two main structural trends: N140º–N170º and N50º–N80º. The dikes have tholeiitic affinities and are composed of plagioclase (An55), augite and augite-pigeonite, relicts of olivine and opaque minerals. These rocks have high contents of Fe–Ti oxides (titanomagnetites), the mineralogical and textural characteristics of which have been studied using scanning electron microscopy and energy dispersive spectrometry techniques (SEM – EDS). These features, along with other mineralogical and textural relationships, have been used to propose the following crystallization sequence for the dikes: (i) crystallization of olivine, plagioclase and Ca-rich pyroxene phenocrysts; (ii) precipitation of the first population of Ti-magnetite; (iii) crystallization of plagioclase and pyroxene in the groundmass; (iv) partial dissolution of Ti-magnetite by reaction with magmatic fluids; (v) crystallization of the second population of Ti-magnetite and finally, (vi) crystallization of interstitial barite.